PRODUCTION OF BIOETHANOL FROM AN AGRO WASTE, PROCESSED ARECA CATECHU WATER - SHOBHA G,; ANANDA S,; VEDA G.,; SHASHIDHARA K.S., (International Journal of Pharma and Bio Sciences, 2016)
Bioethanol is a promising potential renewable energy to petroleum-derived transportation fuel. Ethanol can be produced from a variety of biological sources. Lignocellulosic biomass has been suggested as the most promising alternative for the traditional starch feedstock. Areca nut processed agro waste water is an attractive biomass for bioethanol production due to carbohydrate contents. The biochemical tests of Areca nut agro processed water showed the presence of more of cellulose in the raw material. Saccharification was better When the enzymes, cellulase and amylase were used for hydrolysis, than acid hydrolysis (23.5 mg/ml Glu). The bioethanol production revealed that SSF (Simultaneous Saccharification and fermentation) (11.6 g/L ethanol) process is better as compared to SHF (Separate Hydrolysis and Fermentation) process (9.25 g/L ethanol) in bioethanol production. First time we are showing that the Areca nut processed agro waste water is an attractive biomass for bioethanol production due to its higher carbohydrate contents.